PENGARUH KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI FRESH KAPUAS KOTA BENGKULU - Muhamad Galy Njoman Ari Pribowo; Atika Tri Milinia (Jurnal Cakrawala Ilmiah, 2022)
This study aims 1) To determine the effect of service quality on purchasing decisions at Fresh Kapuas Bengkulu City 2) To determine the effect of price on purchasing decisions at Fresh Kapuas Bengkulu City 3) To determine the effect of location on purchasing decisions at Fresh Kapuas Bengkulu City 4) To determine the influence of service quality, price, and location on purchasing decisions at Fresh Kapuas, Bengkulu City. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all visitors to Fresh Kapuas, Bengkulu City who wanted to buy 50 people a day, a sample of 57 people. Based on the results of research on the influence of service quality, price, and location on purchasing decisions at Fresh Kapuas, Bengkulu City. 1) Service quality (X1) affects consumer purchasing decisions (Y) Fresh Kapuas Bengkulu City with a tsig value of 0.000, thus Ho is rejected and Ha is accepted, which means that the X1 variable affects consumer purchasing decisions (Y). 2) Price (X2) affects purchasing decisions (Y) Fresh Kapuas Bengkulu City with a tsig value of 0.001 thus Ho is rejected and Ha is accepted, which means that X2 variable affects consumer purchasing decisions (Y). 3) Location (X3) affects purchasing decisions (Y) Fresh Kapuas Bengkulu City with a tsig value of 0.002, thus Ho is rejected and Ha is accepted, which means that X2 variable affects consumer purchasing decisions (Y). 4) Quality of service, price and location together affect consumer purchasing decisions with a value of Fsig < where Fsig is 0.000